Replication of an agent-based model using the Replication Standard. (May 2021) - Zhang, Jiaxin; Robinson, Derek T.
Abstract: Despite the critical role that replication plays in the advancement of science, its presence in modelling literature is rare. To encourage others to conduct replication and report success and challenges that facilitate or hinder replication, we present the replication of an agent-based model (ABM) of residential sprawl using the Replication Standard. Replication results achieved relational equivalence. Through the replication process, issues with the original research were identified and corrected in an Improved model, which qualitatively supported original results. A specific challenge affecting alignment of original and Replicate models included capturing model output variability and publishing all original output data for statistical analysis. Through the replication of agent-based models, additional confidence in model behaviour can be garnered and replicated ABMs can become accredited for reuse by others. Future research in the development and refinement of replication methodology and assessments should be cultivated along with a culture of value for replication efforts. Highlights: The relevance and need for model replication is discussed. A methodology for model replication is presented. A case study illustrates application of the replication methodology. Replicate model outcomes are assessed using the Replication Standard. Replication challenges are highlighted and future directions suggested.